THE STRATEGIC BUSINESS ANALYSIS USING PESTEL AND PORTER’S FIVE FORCES MODEL (A Study about 德州美墨炸雞 Rangers Fried Chicken Taipei-Taiwan): Universitas Budi Luhur Jakarta - Nurfauziyah, Yeni; Khalid, Zulvia (Jurnal Ekonomi Bisnis Manajemen dan Akuntansi (JEBISMA), 2024)
This study is a quantitative study by analyzing The Strategic Business Analysis Using Pestel And Porter’s Five Forces Model (A Study About 德州美墨炸雞 Rangers Fried Chicken Taipei-Taiwan), using PESTEL analysis and Porter's Five Forces model with a qualitative approach. The results show that economic stability, technological developments, and changes in consumer preferences provide opportunities and challenges. The tight competition in the fast food restaurant industry is characterized by the presence of international and local players. Adaptive and innovative strategies are needed to maintain competitiveness, including improving product quality, diversifying menus, and adopting the latest technology.